Effects of Boron on Microstructure and Metastable Pitting Corrosion Behavior of Super304H Austenitic Stainless Steel. Issue 9 (25th June 2015) - Bai, Guanshun; Lu, Shanping; Li, Dianzhong; Li, Yiyi
Abstract : The effects of boron on the microstructure and the pitting corrosion behavior, especially the metastable pitting, were investigated in Super304H austenitic stainless steels with 0–130 ppm boron solution treated at 1100°C. The microstructures were analyzed using scanning electron microscopy, transmission electron microscopy with energy dispersive spectroscopy and secondary ion mass spectroscopy. Meanwhile, the pitting corrosion behavior was evaluated by potentiodynamic and potentiostatic polarization tests in 3.5% NaCl solution at 25°C. Microstructural characterizations showed that boron addition favored the precipitation of Cr-rich boride (M2 B), which resulted in an asymmetric Cr-depleted zone around M2 B and reduced the chromium content in the austenite matrix. The Cr-depleted zones could act as extra sites for pit initiation, along with the interfaces between the austenite matrix and non-metallic inclusions. The potentiodynamic polarization test results indicated that boron addition decreased the pitting potential. The potentiostatic test results revealed that boron addition promoted the initiation frequency and growth rate of metastable pits, and increased the probability of stable pitting.